Galectin-3 and Risk of Late Graft Failure in Kidney Transplant Recipients: A 10-year Prospective Cohort Study. Issue 5 (25th June 2020) - Sotomayor, Camilo G.; te Velde-Keyzer, Charlotte A.; Diepstra, Arjan; van Londen, Marco; Pol, Robert A.; Post, Adrian; Gans, Rijk O.B.; Nolte, Ilja M.; Slart, Riemer H.J.A.; de Borst, Martin H.; Berger, Stefan P.; Rodrigo, Ramón; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Galectin-3 may play a causal role in kidney inflammation and fibrosis, which may also be involved in the development of kidney graft failure. With novel galectin-3-targeted pharmacological therapies increasingly coming available, we aimed to investigate whether galectin-3 is associated with risk of late graft failure in kidney transplant recipients (KTR). Methods: We studied adult KTR who participated in TransplantLines Insulin Resistance and Inflammation Biobank and Cohort Study, recruited in a university setting (2001–2003). Follow-up was performed for a median of 9.5 (interquartile range, 6.2–10.2) years. Overall and stratified ( P interaction < 0.05) multivariable-adjusted Cox proportional-hazards regression analyses were performed to study the association of galectin-3 with risk of graft failure (restart of dialysis or retransplantation). Results: Among 561 KTR (age 52 ± 12 y; 54% males), baseline median galectin-3 was 21.1 (interquartile range, 17.0–27.2) ng/mL. During follow-up, 72 KTR developed graft failure (13, 18, and 44 events over increasing tertiles of galectin-3). Independent of adjustment for donor, recipient, and transplant characteristics, galectin-3-associated with increased risk of graft failure (hazard ratios [HR] per 1 SD change, 2.12; 95% confidence interval [CI], 1.63-2.75; P < 0.001), particularly among KTR with systolic blood pressure ≥140 mmHg (HR, 2.29; 95% CI, 1.80-2.92; P < 0.001; P interaction = 0.01) or smoking history (HR, 2.56; 95% CI, 1.95-3.37; P < 0.001; P interaction = 0.03). Similarly, patients in the highest tertile of galectin-3 were consistently at increased risk of graft failure. Conclusions: Serum galectin-3 levels are elevated in KTR, and independently associated with increased risk of late graft failure. Whether galectin-3-targeted therapies may represent novel opportunities to decrease the long-standing high burden of late graft failure in stable KTR warrants further studies. Abstract :